Reductive roasting of iron-rich manganese oxide ore with elemental sulfur for selective manganese extraction - You Z.; Li G.; Peng Z.; Qin L.; Zhang Y.; Jiang T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
It is very important to selectively reduce manganese oxide over iron oxide for extraction of Mn from iron-rich manganese ore. In this study, reductive roasting of an iron-rich manganese oxide ore with elemental sulfur as reductant was investigated. The experimental results demonstrated that manganese dioxide can be selectively reduced with elemental sulfur and extracted via acid leaching, which was largely depended on the sulfur addition. Lower sulfur addition (S/Mn molar ratio<1.0) results in higher selectivity, which is independent of roasting temperature. More than 95% manganese and less than 10% iron were extracted through acid leaching under the roasting conditions of 400-600°C with S/Mn molar ratio of 0.6. The contents of manganese sulfide and sulfate in the roasted product increased with increasing sulfur addition, while they decreased distinctly at temperatures above 550°C. The thermodynamic analysis also proved that manganese dioxide is more easily reduced than iron oxide by sulfur at 300-900 K. The phase transformations during reductive roasting revealed that sulfides (MnS and FeS2) were favored at temperatures lower than 550°C whereas the oxides (MnFe2O4 and Fe3O4) were predominant at higher temperatures. The reduction of iron oxide mainly occurred at large sulfur additions (S/Mn>2.0) and the roasting temperature exerted a significant impact on the phase composition of roasted product.